Circulating tumor cells (CTCs)/circulating tumor endothelial cells (CTECs) and their subtypes in small cell lung cancer: Predictors for response and prognosis. Issue 20 (23rd August 2021) - Zhu, Hao‐Hua; Liu, Yu‐Tao; Feng, Yu; Zhang, Li‐Na; Zhang, Tong‐Mei; Dong, Gui‐Lan; Xing, Pu‐Yuan; Wang, Hong‐Yu; Shi, Yuan‐Kai; Hu, Xing‐Sheng
Abstract: Background: The aim of the study was to define the clinical significance of circulating tumor cells (CTCs)/circulating tumor endothelial cells (CTECs) and their subtypes in small cell lung cancer (SCLC) patients. Methods: CTCs/CTECs and their subtypes were determined using SE‐iFISH technology in 33 SCLC patients before initial treatment (B1), after two cycles of chemotherapy (B2), at the completion of chemotherapy (B3), and disease progression (B4). The correlations with clinical characteristics, progression‐free survival (PFS), and overall survival (OS) were analyzed. Results: CTCs and CTECs were detected in 96.6% and 65.5% of patients, respectively. Patients had higher levels of CTCs compared with CTECs in circulation ( p < 0.05). Extensive‐stage SCLC patients tended to have higher CTEC counts ( p = 0.035), and the detection of CTC‐white blood cell (CTC‐WBC) clusters was associated with a worse response to treatment ( p = 0.030). Patients with CTC‐WBC clusters at B1 (17.3 vs. 22.6 months, p = 0.041) and B2 (19.9 vs. 25.2 months, p = 0.018) had significantly shorter OS than those with no detection. Additionally, their presence was revealed as independent predictors for a worse OS in multivariable analyses (B1: HR 9.3, 95% CI: 1.4–48, p = 0.0079; B2: HR 4.4, 95% CI: 1.1–18, p = 0.041). A high CTC level at B4 was an adverse prognostic factor for SCLC patients (PFS: 8.7 vs. 22.5 months, p = 0.0026; OS: 19 months vs. not reached, p = 0.0086). CTC clusters and CTECs also showed prognostic values. Conclusions: The presence of CTC‐WBC clusters at baseline and after two‐cycle chemotherapy and the total CTC counts at the completion of chemotherapy are strong predictors for the prognostic survival of SCLC patients receiving first‐line treatment. Abstract : It has been proved in many studies that CTCs can be used as a prognostic biomarker in SCLC patients. Here, we report that CTC‐WBC clusters may also be a valuable predictor for SCLC prognosis. In this study, patients with CTC‐WBC clusters before chemotherapy (17.3 vs. 22.6 months, p = 0.041) and after two cycles of treatment (19.9 vs. 25.2 months, p = 0.018) tended to have a significantly shorter overall survival duration.